Secure industrial automation and control systems: Using 4G (LTE) wireless technology - Al-Saeed, Mohammed A; Al-Walaie, Soliman; Alusail, Khalid Y; Al-Anezi, Turki K (InTech, 2016)
[...]4G (LTE) technology with effective security controls and optimized design has the capability and capacity to serve voice, video, and broadband industrial data and applications simultaneously. 4G (LTE) wireless security Generally, oil and gas operations are spread across large geographical areas, and workers at centralized control centers manage and operate day-today field operations, which are subject to harsh environmental conditions. Security observations * LTE technology with effective security controls, such as VPN (IPSec) and GRE, can serve voice, video, and broadband industrial data and applications simultaneously. * 4,000 IPSec tunnels can be configured on the firewall, USG 6370. [...]the firewall can support up to 4,000 remote field sites. * The system throughput decreased by 30 percent using an IPSec tunnel and GRE tunnel. * The POC proved that a secure LTE wireless platform can serve multiple IT and OT systems, such as SCADA and CCTV applications, and allocate the required resources.